Institutions and agricultural transformation: a study of induced innovation in the Philippine rice sector - Montesclaros, Jose Ma. Luis P. (Nanyang Technological University, 2024)
Despite significant support by the Philippine government over the past decades to its rice sector (as a share of GDP), rice productivity growth has lagged behind demand growth, leading to higher domestic rice prices compared to other countries, and worsening food security outcomes. This dissertation analysed this puzzle using the theoretical approach of rational choice institutionalism (RCI), whereby institutions shape individual behaviour, and are also shaped by individual behaviour. The RCI is applied to agriculture through a proposed theory of induced innovation adoption (IIA), which states farmers will adopt innovations so as to produce enough food to meet domestic demand if a conducive institutional setting exists. Three factors hypothesised to serve as institutional barriers that prevent IIA from occurring in the Philippine context include 1) de-facto currency overvaluation, 2) trade protection, and 3) capitalisation challenges. The historical institutionalism theory of path-dependence is further leveraged in understanding the underlying institutional reasons behind the persistence each of the three hypothesised institutional factors. Research methodologies to support the hypotheses included a three-part case-study which leveraged expert interviews; reviews of relevant policy documents; macro-level analysis of international data; and micro-level analysis building on farmer interviews over a 5-decade period published by the International Rice Research Institute. Research findings supported the hypotheses that agricultural transformation was impeded by the three factors: 1) an industrialisation-inspired de-facto currency overvaluation regime removed farmers’ potential to capture export markets, the latter serving as a “carrot” for adopting innovation; 2) trade protectionist policies in the rice sector removed import competition as a “stick” for adopting innovation; and 3) industrialisation- and land reform-related capital scarcity among smallholder farmers hindered the dynamics of IIA from taking place. The analysis also traced the persistence of these policies back to the state’s premature turn to industrialisation (Post-World War II era) even before the country’s rice sector could be made competitive: historical industrialisation policies 1) created initial conditions for currency overvaluation, and 2) set the stage for the outflow of financial resources from agriculture, leading to capitalisation challenges of farmers; 3) currency overvaluation in turn necessitated policies to protect the market share of farmers from trade (import) competition. Problems from each of the three institutions thus aggravate one another, within a “capital-trade-technology nexus” impacting the Philippine rice sector; similarly, solutions to one of these issues contribute to solving the others. The 2019 Rice Tariffication Law is highlighted as a key “path-breaking” event which contributed to addressing not only the rice trade protectionism problem but also in part the farmers’ capitalisation problems. These findings imply the need for more nuanced approaches in promoting agricultural transformation which consider the roles of broader macroeconomic policies and their lingering impacts, to more effectively “securitise” the food sector.